(+)‐9‐Benzyloxy‐α‐Dihydrotetrabenazine as an Important Intermediate for the VMAT2 Imaging Agents: Absolute Configuration and Chiral Recognition. Issue 4 (26th March 2013) - liu, Chunyi; Chen, Zhengping; Li, Xiaomin; Tang, Jie; Qin, Xiaofeng
ABSTRACT This article reports, for the first time, on the absolute configuration of (+)‐9‐benzyloxy‐α‐dihydrotetrabenazine (8), as determined from the perspective of X‐ray crystallography. Compound 8 was prepared by a six‐step reaction using 3‐benzyloxy‐4‐methoxybenzaldehyde (1) as a starting material. The X‐ray crystal diffraction structure of two compounds, racemic 9‐benzyloxy‐tetrabenazine (5) and the diastereomeric salt of compound 8, is also described for the first time in this article. The X‐ray results and the chiral HPLC helped elucidate that compound 8 has an absolute configuration as 2R, 3R, 11bR. The crystal structure of racemic compound 5 contains two symmetry‐ independent molecules in the unit cell. Interestingly, while they are structural isomers, they are enantiomers, too, i.e., in solution, because they are not mirror images of each other in the crystal lattice. In order to elucidate the intermolecular interaction mechanism of the diastereomeric salt of compound 8, its crystal packing was investigated with regard to the weak interactions, such as salt bridge, OH…O and CH…O hydrogen bonds, and intermolecular CH…π interaction. The results showed that the carbonyl‐assisted salt bridges and the OH…O hydrogen bonds formed polar columns in the crystal structure of the diastereomeric salt of compound 8, resembling butterflies with open wings as viewed along the c‐axis. These polar columns were extended to three‐dimensional network by intermolecular CH…O hydrogen bonds and intermolecular CH…π interactions. Chirality, 2013. © 2013 Wiley Periodicals, Inc.